Growth and characterization of graphene and graphene/copper oxide nanocomposites by hot-filament thermal chemical vapor deposition for flexible pressure sensor application / Syed Muhammad Hafiz Syed Mohd Jaafar - Syed Muhammad Hafiz , Syed Mohd Jaafar (2017)

(untitled)
Graphene is an emerging two-dimensional carbon nanostructure which is composed of sp2 hybridized carbon atoms arranged in a hexagonal lattice. After the remarkable observations of the unique properties of graphene surfaced in the past decade, tremendous interest in the scientific community on this material has led to various investigations on the preparation techniques as well as its potential application. This thesis reports the top-down and bottom-up approach of fabrication of graphene and its application in gas and pressure sensor devices. Three types of graphene-based materials are produced in this work which includes reduced graphene oxide (GO), high-quality graphene and graphene/Cu2O nanocomposites. The top-down approach of graphene fabrication used in this work started with GO where graphite flakes are oxidized using the simplified hummers method. This process initiates exfoliation of graphite layers by weakening the van der Waals forces in between its layers by introducing oxygen functional groups. GO is an insulating material, thus the top-down approach of growing graphene here involves the removal of these functional groups to restore its conductivity which is indeed a challenging task. Hydrogen plasma treatment is employed to reduce the GO into reduced graphene oxide (rGO) as an alternative to using hydrazine solution which is known to be toxic. The effectiveness of hydrogen plasma treatment to remove oxygen functional groups is systematically evaluated in terms of its morphology, topological, structural and elemental composition before and after the reduction process. The optimized rGO is used as the sensing material in a carbon dioxide (CO2) gas sensor and the sensing capabilities are assessed. The tests are performed in dry and humid environment in the range of 0 to 1500 ppm (parts per million) of CO2 which match closely to the indoor air quality monitoring environment. The catalytic chemical vapour deposition (Cat-CVD) technique is a simple, low cost, bottom-up approach of growing graphene but have been reported to have the disadvantage of producing high defect density graphene, In this work, the Cat-CVD system is modified and a novel growth technique of growing graphene and graphene/Cu2O nanocomposite is introduced. This novel technique is referred to as the hot-filament thermal CVD (HFTCVD). In this technique, a close ended alumina tube wound with tungsten filament is connected to the low voltage connections via the ends of the tungsten coil replacing the hot-filament of the Cat-CVD system. The production of graphene samples by varying the growth duration and hydrogen flow rate is systematically studied with respect to its morphology, topological, structural and elemental composition. The effects of catalytic dissociation of methane and hydrogen gas at tungsten filament temperature above 1500 °C in quasi-static equilibrium copper vapour inside the alumina tube on the properties of graphene are studied and analysed. High quality graphene with ID/IG ratio of ~0.1 was successfully produced on Cu foils. The growth mechanism of graphene growth by this technique is proposed. The substrate temperature played an important role in growing graphene/Cu2O nanocomposites, shown in this work to be a promising material for highly sensitive flexible pressure sensor. The effects of substrate temperature are studied with respect to structure, morphology and electrical properties of the graphene/Cu2O nanocomposites. The graphene/Cu2O nanocomposites sample is tested for use as a sensing material in flexible pressure sensor for its sensing capability. The piezoresistive effects are systematically evaluated for applied pressure within a wide range of 0 to 50 kPa. The sensor sensitivity, sensing and recovery time, limit of detection and gauge factor criteria are measured. The sensing mechanism is proposed to provide a better understanding on the use of graphene-based material in highly sensitive piezoresistive-based flexible pressure sensors device.